2011
DOI: 10.1111/j.1744-1609.2011.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of registered nurses as managers and leaders in residential aged care facilities: a systematic review

Abstract: Overall the themes presented in the review reported the negative experiences of nurses in residential aged care and geriatrics. Nurses will continue to be devalued if there is no professional identity and support for their roles and need to have a career pathway when making the decision to enter into aged and geriatric practice. Clinical leadership training is needed for nurses to transition through practice into specialised roles such as the RN team leader and Geriatric Nurse Practitioner (GNP). Providing a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
118
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(119 citation statements)
references
References 25 publications
1
118
0
Order By: Relevance
“…A systematic review of experiences of registered nurses as managers and leaders in residential aged care facilities found nurses experienced a lack of professional support and collaboration from allied health and medical colleagues [23]. In the same review, organisation was identified as a barrier in preventing continuing education and skills development for nurse leaders in aged care settings [23].…”
Section: Discussionmentioning
confidence: 98%
“…A systematic review of experiences of registered nurses as managers and leaders in residential aged care facilities found nurses experienced a lack of professional support and collaboration from allied health and medical colleagues [23]. In the same review, organisation was identified as a barrier in preventing continuing education and skills development for nurse leaders in aged care settings [23].…”
Section: Discussionmentioning
confidence: 98%
“…In response to these challenges, modern healthcare is looking for ways to treat patients that are both more efficient as well as more cost saving (Young et al 2014;Fu et al 2010;Dwyer 2011). It has to be taken into account that these improvements are expected to be managed without the necessary care that patients demand today.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, to simultaneously see beyond a disease driven discourse and envisage a health ageing model optimising functional and cognitive capability (WHO, 2015). New models of care are emerging and it is nursing that adds some of the fundamental dimensions to such models that contributes to well-being for older people and carers (Dwyer 2011;Ament et al, 2015). However, lack of investment in post-registration education and opportunities to develop higher level professional attributes limits the scalability of new models of care (Huston 2008, Houde andMelillo 2009;Huizenga et al 2016).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The broad based expertise and diverse career and education pathways of the Fellows reflects the lack of a standardised approach to developing a workforce to match changing population needs (Dwyer 2011;Goldberg et al, 2016). The rich diversity of background and experiences contributed significantly to peer-to-peer learning but posed challenges in designing a curriculum that met all participants'…”
Section: Accepted M Manuscriptmentioning
confidence: 99%